DEVELOPMENT OF HULL CRACK DETECTION USING IMAGE PROCESSING FOR HULL INSPECTION - Atzroulnizam Abu; Iffah Munirah Mohd Saiful Asri Apparau; Muhammad Fadli Ghani; Mohd Saidi Hanaffi; Ahmad Zawawi Jamaluddin (Marine Frontier, 2021)
The crack on the ship hull might cause huge harm and disaster towards a vessel. The crack might affect the safety and performance of the vessels. Nowadays, hull inspection is being done by a human being. This may cause some errors and miss inspection area of the hull. With the application of the technology wave, the usage of computer vision technology is needed in this field. This research aims to develop a crack detection system by using image processing for ship deficiency using MATLAB software. Then, a suitable image processing method is being analyzed to enhance the quality of the image for different situations. In this research, the Sobel edge detection operator is being used as the most accurate and precise operator among the three classic operators. It is the most convenient and less time-consuming operator that can be used and has been used in the civil field.